2001
DOI: 10.1002/sim.684
|View full text |Cite
|
Sign up to set email alerts
|

Assigning time‐linked exposure status to controls in unmatched case‐control studies: alcohol use and nearly lethal suicide attempts

Abstract: In case‐control studies, determination of alcohol consumption by cases immediately prior to the injury event is often conceptually straightforward. However, determination of consumption status by controls is difficult because they lack a reference point, especially when cases and controls are not individually matched. We describe a method of assigning alcohol consumption status to controls using a 24‐hour drinking history, the distribution in time of case events, and the random assignment of a specific time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Vinson et al 20 showed in case-control and case-crossover analyses that odds ratios for violence-related injuries are especially high when the injury is associ--ated with alcohol use during the 6 hours prior to injury (OR = 34; 95% CI = 4.7-250); this finding has been reported by others 6,36,44,45 and confirmed by this research. The risk of suicide attempts was especially high in our study, confirming a more limited finding from a frequency analysis of a case-crossover study in a sample of patients from Australia, Canada, Mexico and the United States 46 as well as a study in Texas 47 and a hospital-based case-control study in Mexico City. 48 Previous case-crossover reports 1 have reported higher, but not statistically significant, ORs for mo--tor vehicle accidents, falls and "other injuries".…”
Section: Research Guilherme Borges Et Al Alcohol Use and Injuries Trsupporting
confidence: 89%
“…Vinson et al 20 showed in case-control and case-crossover analyses that odds ratios for violence-related injuries are especially high when the injury is associ--ated with alcohol use during the 6 hours prior to injury (OR = 34; 95% CI = 4.7-250); this finding has been reported by others 6,36,44,45 and confirmed by this research. The risk of suicide attempts was especially high in our study, confirming a more limited finding from a frequency analysis of a case-crossover study in a sample of patients from Australia, Canada, Mexico and the United States 46 as well as a study in Texas 47 and a hospital-based case-control study in Mexico City. 48 Previous case-crossover reports 1 have reported higher, but not statistically significant, ORs for mo--tor vehicle accidents, falls and "other injuries".…”
Section: Research Guilherme Borges Et Al Alcohol Use and Injuries Trsupporting
confidence: 89%
“…7,29 Although unintentional injury was the most common for both male and female youth, the second most common intent for male youth was violence-related, and for female youth was self-harm. These results support the broader literature on the role of alcohol as a known risk factor for intentional injuries, 18,30,31 and to the unique role that alcohol plays in the injury experiences of male and female youth. [21][22][23] These findings suggest that injury prevention programs should recognize the differences between the effect of alcohol use on injury outcomes in male and female youth.…”
Section: Discussionsupporting
confidence: 85%
“…Control‐subjects were randomly assigned a 3‐hour period based on the distribution of attempt‐times for the case‐subjects who attempted on that day of the week. The control‐subjects' drinking status (yes/no) was based on whether they reported drinking during that 3‐hour period (Kresnow et al, 2001).…”
Section: Methods and Datamentioning
confidence: 99%